Analisis Kesulitan Mahasiswa dalam Menulis Karya Ilmiah di Program Studi Tadris Bahasa Indonesia - Hosniyeh, Hosniyeh (Jurnal Tinta, 2025)
This study aims to identify various difficulties faced by final semester students of the Indonesian Language Education Study Program in writing scientific papers. The method used in this study is descriptive qualitative. The primary data in this study are the results of answers to questionnaires distributed by researchers to representatives of 10 students who have finished writing scientific papers in the Indonesian Language Education Study Program. while the data collection techniques used in this study are: interviews, questionnaires and documentation. The data analysis techniques in this study consist of three flows, namely data reduction, data presentation, and drawing conclusions. The results of this study are that the majority of respondents experience various difficulties in writing scientific papers, both in technical aspects and understanding the material. As many as 90% of respondents found it difficult to formulate a title, As many as 80% of respondents found it difficult to compile a research background, As many as 70% of respondents found it difficult to find references, As many as 90% of respondents found it difficult to compile a theoretical framework, As many as 90% of respondents found it difficult to understand research methods, As many as 90% of respondents found it difficult to analyze data, As many as 80% of respondents found it difficult to use standard language, As many as 90% of respondents found it difficult to write sentences and paragraphs, As many as 70% of respondents found it difficult to use punctuation. This shows that students need more intensive and structured guidance, as well as direct training to improve their skills in writing scientific papers. That way, it will produce quality scientific papers.